Bonding strength high-throughput testing method

Test components are prepared through 3D printing technology and combined with a high-throughput testing platform, the problems of low efficiency of traditional bonding performance testing and inconsistent sample preparation are solved, and efficient and accurate bonding strength testing is achieved, which is suitable for simulating multi-axis load conditions in complex practical applications.

CN119618992AActive Publication Date: 2025-03-14XI AN JIAOTONG UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411751926.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-14
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

Traditional bonding performance testing methods are inefficient and inconsistent sample preparation, making it difficult to simulate multi-axis loading conditions in complex practical applications, affecting the reliability and consistency of data.

Method used

Test components are prepared using 3D printing technology, combined with a high-throughput testing platform, and efficient and accurate bond strength testing is achieved through automated data acquisition and image processing.

Benefits of technology

It greatly improves the efficiency and accuracy of bonding performance testing, ensures the consistency and repeatability of test results, and can simulate multi-axis load conditions and accelerate the research and development and quality control process of adhesives and related products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119618992A_ABST
    Figure CN119618992A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of bonding strength testing methods, and particularly relates to a bonding strength high-throughput testing method which comprises the following steps: a testing assembly is prepared by adopting 3D printing, the testing assembly comprises two rectangular strips, a plurality of testing samples are arranged between the two rectangular strips, each testing sample comprises two testing structures, and the testing structures are arranged on the rectangular strips; each test structure comprises a first substrate, a second substrate and a force measurement module, the first substrate is provided with bonding surfaces, and the two bonding surfaces are connected through an adhesive to form a joint; acting force is applied to the rectangular strips until bonding fails; a video recording module is adopted to record the change of the test assembly in the whole process, and an initial test image and an image when bonding fails are obtained; an image processing module is adopted to process the images to obtain the strain of the force measurement module; and obtaining a corresponding maximum load through a force-displacement curve. According to the invention, a 3D printing technology and a high-throughput test platform are combined, and an efficient, accurate and systematic method is provided for performance evaluation of the adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bonding strength testing methods, and in particular relates to a high-throughput bonding strength testing method. Background Art

[0002] Adhesives are widely used in various industrial fields, such as automotive manufacturing, aerospace, construction engineering and electronic assembly. The performance of adhesives directly affects the quality and safety of the final product. In order to ensure that the performance of adhesives can meet the needs of specific applications, they must be subjected to rigorous performance testing. These tests not only need to evaluate the basic physical and chemical properties of adhesives, such as viscosity, curing time and chemical stability, but also their mechanical properties under actual application conditions, such as tensile strength, shear strength and fatigue resistance. As industry's requirements for bonding performance continue to increase, it becomes crucial to systematically and comprehensively evaluate and optimize the performance of adhesives.

[0003] Traditional adhesive performance testing often requires a lot of manual work and time to prepare and test individual samples. This greatly limits the throughput of the test and prolongs the product development cycle. Due to the inherent uncertainties in manual sample preparation, such as slight differences in adhesive coating thickness and curing conditions, test results are often difficult to reproduce, affecting the reliability and consistency of the data. Most existing testing equipment can only evaluate a single mechanical loading condition (such as pure tension or pure shear) and cannot simulate the multi-axial loading conditions that may be encountered in complex actual applications. The above factors limit the improvement of the efficiency and accuracy of adhesive performance testing and slow down the research and development and quality control process of adhesives and related products. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a high-throughput testing method for bonding strength, which combines 3D printing technology and a high-throughput testing platform solution, aiming to overcome the limitations of the prior art and provide a new, efficient, accurate and systematic method for the performance evaluation of adhesives, thereby accelerating the research and development and quality control process of adhesives and related products.

[0005] The present invention is achieved through the following technical solutions.

[0006] A high-throughput test method for bonding strength comprises the following steps:

[0007] A test assembly is prepared by using 3D printing technology, and the test assembly includes two rectangular bars, and a plurality of test specimens are arranged in parallel between the two rectangular bars, each of the test specimens includes two test structures, and each of the test structures includes a first substrate, a second substrate and a force measurement module, and the force measurement module is fixedly connected between the first substrate and the second substrate, and the first substrate has a bonding surface, and the two bonding surfaces are connected by an adhesive to form a joint.

[0008] The test component is placed in a test environment, and a force is applied to the rectangular bar to stretch the force measurement module to generate strain until the joint adhesion fails. During the test, a video recording module is used to record the changes of the test component throughout the process, and an image at the beginning of the test and an image at the time of adhesion failure are obtained.

[0009] The image at the beginning of the test and the image at the time of bonding failure are processed respectively by an image processing module to obtain the length of each force measurement module at the beginning of the test and at the time of bonding failure, and the strain of the force measurement module when the joint reaches the maximum load is calculated.

[0010] The strain is substituted into the force-displacement curve of the force measurement module to obtain the corresponding maximum load, and then the bonding strength of the joint is obtained.

[0011] Preferably, the adhesive is a material for 3D printing or a material not for 3D printing.

[0012] When the adhesive is a material for 3D printing, the test component is integrally prepared by one 3D printing.

[0013] When the adhesive is a material not used for 3D printing, the first assembly and the second assembly are prepared respectively by 3D printing technology, and the first assembly and the second assembly respectively include one of the rectangular strips and a plurality of the test structures; in the first assembly, the first substrate of each test structure has a first bonding surface; in the second assembly, the first substrate of each test structure has a second bonding surface; the first assembly and the second assembly are assembled through an assembly plate, and the first bonding surface and the second bonding surface are connected by an adhesive to form a joint.

[0014] Preferably, the assembly plate comprises a bottom plate, a plurality of first positioning strips are arranged in parallel along the length direction on the surface of the bottom plate, and the space between two adjacent first positioning strips is used to limit a test structure in the first assembly.

[0015] The bottom plate surface is also provided with a plurality of second positioning bars arranged in parallel along the length direction, the second positioning bars correspond to the first positioning bars one by one, and two adjacent second positioning bars are used to limit a test structure in the second assembly.

[0016] A plurality of positioning protrusions arranged along the length direction of the bottom plate are also arranged between the first positioning strip and the second positioning strip, and the plurality of positioning protrusions are arranged close to one side of the first positioning strip, and between two adjacent positioning protrusions, a first bonding surface is limited. A limiting strip is also arranged between the first positioning strip and the second positioning strip, and the limiting strip is arranged close to one side of the second positioning strip, and is used to adjust the bonding thickness between the second bonding surface and the first bonding surface.

[0017] The two ends of the bottom plate are respectively provided with first limiting grooves on one side of the first positioning strip, and the two first limiting grooves are used to limit the rectangular strip in the first assembly; the two ends of the bottom plate are respectively provided with second limiting grooves on one side of the second positioning strip, and the two second limiting grooves are used to limit the rectangular strip in the second assembly.

[0018] Preferably, the method of assembling the first assembly and the second assembly comprises the following steps:

[0019] After dipping the first adhesive surface in adhesive, the test structures in the first assembly are respectively placed between the first positioning strips. When the rectangular strips in the first assembly are limited by the two first limiting grooves, the first adhesive surface is placed between adjacent positioning protrusions.

[0020] After dipping the second bonding surface in adhesive, the test structures in the second assembly are placed between the second positioning strips respectively. When the rectangular strips in the second assembly are limited by the two second limiting grooves, the bottom surface of the second bonding surface is placed on the limiting strips and contacts the first bonding surface for bonding.

[0021] Preferably, the test background is black, the first substrate and the second substrate are white, and the processing method of the image processing module comprises the following steps:

[0022] Screenshot software was used to capture the video frame by frame. Taking 4k photos as an example, MATLAB was used to process each image into a 3840×2160 matrix. Each element in the matrix represented the grayscale of a pixel. Then the elements of the matrix were binarized: 255 represented a grayscale pixel close to white, and 0 represented a grayscale pixel close to black.

[0023] Based on the white first substrate and the white second substrate, all pixels with grayscale values ​​lower than 200 are set to 0; the first substrate image is extracted to locate the left and right boundaries of each test sample; the method for locating the left and right boundaries of each test sample is as follows: summing the grayscale image columns to obtain the total grayscale pixel value of each column, and in two adjacent columns, from left to right, when the total grayscale pixel value changes from small to large, it is the left boundary of a sample, and when the total grayscale pixel value changes from large to small, it is the right boundary of a sample.

[0024] The white second base image is extracted to locate the upper and lower boundaries of each test sample; the method for obtaining the upper and lower boundaries of each test sample is: row summing of the grayscale image to obtain the total value of the grayscale pixels in each row, and in two adjacent rows, from top to bottom, when the total value of the grayscale pixels changes from small to large, it is the upper boundary of a sample, and when the total value of the grayscale pixels changes from large to small, it is the lower boundary of a sample.

[0025] By obtaining the left and right boundaries and the upper and lower boundaries of each test sample, the position information of each test sample is determined, and the image of the test sample is extracted according to the position information of each test sample and placed in a matrix to obtain the upper and lower boundaries of the force measurement module in each test sample, and the length of the force measurement module in each test sample is calculated. For example, taking the first sample as an example, its image is extracted according to its position information and placed in a small matrix. In this way, only the small matrix needs to be analyzed to find the upper and lower boundaries of the force measurement module, and the length of the force measurement module can be calculated in real time. By performing this processing on multiple photos at the same time, the changes in the force measurement modules of multiple samples in the entire experiment can be obtained.

[0026] Preferably, the first substrate and the second substrate are made of a rigid resin material VeroPureWhite by 3D printing, and the force measurement module is made of a 3D printed linear elastic material.

[0027] Preferably, the test method is used to optimize the preparation parameters of the adhesive, and the adhesives in the plurality of test samples are prepared with different parameters respectively; or:

[0028] The test method is used to explore the influence of adhesive layer thickness and different stress modes on adhesive failure strength and failure mode. At this time, multiple test specimens are grouped so that the adhesives in each group have different thicknesses, and the adhesives in the same group have the same thickness, but the joints have different bonding angles. For example: the number of test specimens is 180, which are divided into 12 groups according to the thickness of 0.1mm to 1.6mm, each group contains 15 test specimens, and the bonding angles of the 15 test specimens in each group are set according to 0° to 90°.

[0029] It should be noted that during the test, the temperature of the test environment is controlled to be -20°C to 60°C; the humidity environment is controlled to be 0 to 100%.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] Compared with the existing bonding strength testing technology, the present invention uses 3D printing technology to prepare test samples, and can test a large number of samples at the same time in one test, ensuring the consistency and repeatability of the test process, and uses automated data collection and analysis methods to improve the test efficiency while also improving the test accuracy.

[0032] Since a large number of samples can be tested at the same time, samples with different test conditions can be prepared according to test needs. For example, by changing the joint angle, the adhesive can be placed in different stress modes, simulating multi-axial load conditions that may be encountered in complex practical applications, changing the adhesive thickness to test the influence of thickness, and screening the adhesive preparation process parameters, etc., which can not only greatly improve the efficiency and reliability of bonding performance testing, but also accelerate the research and development and quality control process of adhesives and related products. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 A schematic diagram of the test component structure.

[0034] Figure 2 Schematic diagram of the test specimen structure.

[0035] Figure 3 This is a photo of the initial state of high-throughput testing.

[0036] Figure 4 Status photos for high-throughput bonding testing.

[0037] Figure 5 Schematic diagram of the high-throughput bonding strength characterization process, where (a) the state of the sample before and during the experiment, and (b) the force-displacement curve of the force measurement module.

[0038] Figure 6 It is a schematic diagram of the assembly board structure.

[0039] Figure 7 This is a schematic diagram of the operation of assembling the first assembly part.

[0040] Figure 8 This is a schematic diagram of the operation of assembling the second assembly part.

[0041] Fig. 9 The figure shows the adjustment of the tensile-shear coupling stress ratio of the bonding layer in Example 1, wherein (a) is the distribution of 12 adhesive thicknesses, (b) is the arrangement of different joint angles with a thickness of 0.4 mm at C in (a), (c) is a schematic diagram of the lap shear test at θ=0°, (d) is a schematic diagram of the pull-out test at θ=90°, (e) is a schematic diagram at θ=45°, and (f) is a schematic diagram of the tensile-shear stress decomposition. In the above figures, h is the adhesive thickness and F is the load.

[0042] Fig.10This is the experimental result obtained from a high-throughput experiment in Example 1. DETAILED DESCRIPTION

[0043] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.

[0044] The present invention designs a corresponding high-throughput bonding test specimen based on the lap shear bonding test method. In order to facilitate the batch preparation of high-throughput test specimens, the present invention combines 3D printing technology and uses the printable rigid resin material VeroPureWhite as the specimen body and the bonded substrate. A single row of high-throughput bonding specimens can contain 30 to 60 independent bonding test joints, wherein the geometric structural features of each independent joint (such as bonding layer thickness, joint deflection angle, etc.) can be independently designed during the modeling process; all independent joints in a single row are connected in parallel during the printing process, which will facilitate the subsequent simultaneous loading of these joints.

[0045] For each independent joint, it will use the test principle of build-shear to obtain the bonding failure strength. The two ends of the joint are connected to the clamped end through a force measurement module, which is made of 3D printed linear elastic material. During the loading process, by recording the maximum strain of the force measurement module and corresponding to the force-displacement curve of the material, the maximum failure load of the entire bonding joint during the loading process can be determined, and then the bonding failure strength of the joint can be calculated.

[0046] Based on the above design ideas, the present invention provides a high-throughput test method for bonding strength, which specifically includes the following steps:

[0047] Step 1: Use 3D printing technology to prepare a test component 4, the structure of which is as follows: Figure 1 and Figure 2 As shown, the test assembly 4 includes two rectangular bars 1, and a plurality of test specimens 2 are arranged in parallel between the two rectangular bars 1. Each of the test specimens 2 includes two test structures, and each of the test structures includes a first substrate 3-1, a second substrate 3-2 and a force measurement module 3-3. The force measurement module 3-3 is fixedly connected between the first substrate 3-1 and the second substrate 3-2. The first substrate 3-1 has a bonding surface, and the two bonding surfaces are connected by an adhesive 3-4 to form a joint.

[0048] Step 2: Place the test assembly 4 in a high-throughput bonding test bench for testing, clamp the high-throughput sample to be tested on a high-precision displacement table, and load the sample as a whole by uniformly moving the displacement table, wherein the loading speed is adjustable. Apply force to the rectangular bar 1 to stretch the force measurement module 3-3 to generate strain until the joint fails to bond; during the test, use a video recording module to record the changes of the test assembly throughout the process, and obtain images at the beginning of the test and images at the time of bonding failure.

[0049] It should be noted that the above-mentioned bonding failure refers to the phenomenon that the bonding interface or adhesive loses its original bonding performance under the action of external forces (such as tension, shear or peel force, etc.). Bonding failure is not only related to the properties of the bonding material, but is also affected by many factors such as the bonding process, the treatment of the bonding interface, and the use environment (such as temperature, humidity). Bonding failure can be divided into several different types, mainly including: Bonding interface failure: Failure occurs between the adhesive and the surface of the bonded material, and the insufficient adhesion between the adhesive and the material surface leads to detachment. Adhesive cohesive failure: Failure occurs inside the adhesive, which is manifested as the destruction of the adhesive itself, rather than separation from the interface with the bonded material. Mixed failure: The situation that includes the above two failure modes is the most common type of failure.

[0050] Take the simultaneous testing of 30 test specimens as an example, the initial state photo of the test is as follows: Figure 3 As shown, the status photos during the test are as follows Figure 4 shown. Figure 3 and Figure 4 In the figure, the direction of the arrow is the load direction.

[0051] Step 3: Use an image processing module to process the image at the beginning of the test and the image at the time of adhesion failure, respectively, to obtain the length of each force measurement module 3-3 at the beginning of the test and at the time of adhesion failure, and calculate the strain of the force measurement module 3-3 when the joint reaches the maximum load, where some images are as follows: Figure 5 As shown in (a), the length of the force measurement module 3-3 before the experiment is L, the length when the bonding fails during the experiment is λL, and the strain △L is obtained by calculation.

[0052] Step 4: Substitute the strain into the force-displacement curve of the force measurement module 3-3 to obtain Figure 5 Taking the curve shown in (b) as an example, the corresponding maximum load is obtained, and then the bonding strength of the joint is obtained.

[0053] The method provided by the present invention has the following advantages:

[0054] 1. Large-scale sample testing capability: Through 3D printing technology and automated equipment, the present invention can prepare dozens to hundreds of test samples in a short period of time, and can test these samples simultaneously in one experiment, greatly improving the experimental efficiency.

[0055] 2. Diversified stress modes: Different from the prior art that can only test a single stress mode of the bonding specimen, the present invention can simultaneously test the bonding performance of tension, shear and their coupled stress modes, providing an important experimental basis for comprehensively evaluating the performance of adhesives under different working conditions.

[0056] 3. High precision and high consistency: The present invention realizes precise control of the thickness of the bonding layer, the force mode and the curing conditions through automated control and precise 3D printing technology, thus ensuring the consistency of sample preparation and the high repeatability of the experimental results, and solving the problem of large errors in traditional manual operations.

[0057] 4. Efficient data acquisition and analysis: The present invention integrates advanced image processing technology, which can automatically collect the data of failure strength and failure mode of each sample, and perform rapid processing and analysis, which significantly improves the efficiency and accuracy of data acquisition.

[0058] In summary, the present invention not only solves the problems of low efficiency, inconsistent sample preparation, and difficulty in data collection in the prior art, but also expands the dimension of bonding performance testing, providing a more comprehensive and systematic solution for the design and optimization of adhesives.

[0059] It should be further explained that the adhesive 3-4 is a material for 3D printing or a material not for 3D printing; when the adhesive 3-4 is a material for 3D printing, the test component 4 is prepared as a whole by one 3D printing; when the adhesive 3-4 is a material not for 3D printing, the first assembly 4-1 and the second assembly 4-2 are prepared respectively by 3D printing technology, and the first assembly 4-1 and the second assembly 4-2 respectively include one rectangular strip 1 and a plurality of the test structures; in the first assembly 4-1, the first base 3-1 of each test structure has a first bonding surface A; in the second assembly 4-2, the first base 3-1 of each test structure has a second bonding surface B; the first assembly 4-1 and the second assembly 4-2 are assembled through an assembly plate, and the first bonding surface A and the second bonding surface B are connected by the adhesive 3-4 to form a joint. The first substrate 3 - 1 and the second substrate 3 - 2 are made of a rigid resin material VeroPureWhite by 3D printing, and the force measurement module 3 - 3 is made of a 3D printed linear elastic material.

[0060] In order to facilitate assembly, in a preferred embodiment of the present invention, the assembly plate is designed as follows: Figure 6 to Figure 8As shown, the assembly plate includes a bottom plate 5, and a plurality of first positioning bars 5-1 are arranged in parallel along the length direction on the surface of the bottom plate 5, and the space between two adjacent first positioning bars 5-1 is used to limit a test structure in the first assembly 4-1.

[0061] The surface of the bottom plate 5 is also arranged in parallel along the length direction with a plurality of second positioning bars 5-2, each of the second positioning bars 5-2 corresponds to the first positioning bars 5-1 one by one, and two adjacent second positioning bars 5-2 are used to limit a test structure in the second assembly 4-2.

[0062] A plurality of positioning protrusions 5-3 arranged along the length direction of the bottom plate are also arranged between the first positioning strip 5-1 and the second positioning strip 5-2. The plurality of positioning protrusions 5-3 are arranged close to one side of the first positioning strip 5-1, and the space between two adjacent positioning protrusions 5-3 is used to limit a first bonding surface A. A limiting strip 5-6 is also arranged between the first positioning strip 5-1 and the second positioning strip 5-2. The limiting strip 5-6 is arranged close to one side of the second positioning strip 5-2 and is used to adjust the bonding thickness between the second bonding surface B and the first bonding surface A.

[0063] The two ends of the bottom plate 5 are respectively provided with first limiting grooves 5-4 on one side of the first positioning strip 5-1, and the two first limiting grooves 5-4 are used to limit the rectangular strip 1 in the first assembly 4-1; the two ends of the bottom plate 5 are respectively provided with second limiting grooves 5-5 on one side of the second positioning strip 5-2, and the two second limiting grooves 5-5 are used to limit the rectangular strip 1 in the second assembly 4-2.

[0064] In specific operation, the assembling method of the first assembly 4-1 and the second assembly 4-2 includes the following steps:

[0065] After dipping the first adhesive surface A in the adhesive 3-4, the test structures in the first assembly 4-1 are respectively placed between the first positioning strips 5-1. When the rectangular strip 1 in the first assembly 4-1 is limited by the two first limiting grooves 5-4, the first adhesive surface A is placed between the adjacent positioning protrusions 5-3.

[0066] After dipping the second bonding surface B in the adhesive 3-4, the test structures in the second assembly 4-2 are respectively placed between the second positioning strips 5-2. When the rectangular strip 1 in the second assembly 4-2 is limited by the two second limiting grooves 5-5, the bottom surface of the second bonding surface B is placed on the limiting strip 5-6 and contacts the first bonding surface A for bonding.

[0067] In a preferred embodiment of the present invention, in order to facilitate image processing, the test background is set to black, the first substrate 3-1 and the second substrate 3-2 are white, and the processing method of the image processing module includes the following steps:

[0068] (1) Screenshot software is used to capture the video frame by frame. Taking 4k photos as an example, MATLAB is used to process each image into a 3840×2160 matrix. Each element in the matrix represents the grayscale of a pixel. Then, the elements of the matrix are binarized: 255 represents a grayscale pixel close to white, and 0 represents a grayscale pixel close to black.

[0069] (2) Based on the white first substrate 3-1 and the white second substrate 3-2, all pixels with grayscale values ​​lower than 200 are set to 0.

[0070] (3) The image of the first substrate 3-1 is extracted, and the left and right boundaries of each test sample 2 are located; the method for locating the left and right boundaries of each test sample 2 is: summing the grayscale image columns to obtain the total grayscale pixel value of each column. In two adjacent columns, from left to right, when the total grayscale pixel value changes from small to large, it is the left boundary of a sample 2, and when the total grayscale pixel value changes from large to small, it is the right boundary of a sample 2.

[0071] (4) The white second substrate 3-2 image is extracted to locate the upper and lower boundaries of each test sample 2; the method for obtaining the upper and lower boundaries of each test sample 2 is: perform row summation on the grayscale image to obtain the total value of the grayscale pixels in each row. In two adjacent rows, from top to bottom, when the total value of the grayscale pixels changes from small to large, it is the upper boundary of a sample 2, and when the total value of the grayscale pixels changes from large to small, it is the lower boundary of a sample 2.

[0072] (5) By obtaining the left and right boundaries and the upper and lower boundaries of each test sample 2, the position information of each test sample 2 is determined, and the image of the test sample 2 is extracted according to the position information of each test sample 2 and placed in a matrix, the upper and lower boundaries of the force measurement module 3-3 in each test sample 2 are obtained, and the length of the force measurement module 3-3 in each test sample 2 is calculated.

[0073] The test method provided by the present invention is used to optimize the preparation parameters of the adhesive. In this case, the adhesives in the multiple test samples are prepared by different parameters. The test method of the present invention can also be used to explore the influence of the thickness of the adhesive layer and different force modes on the failure strength and failure mode of the adhesive. In this case, the multiple test samples 2 are grouped so that the adhesives between each group have different thicknesses, and the adhesives in the same group have the same thickness, but the joints have different bonding angles. During the test, the temperature of the test environment is controlled to be -20℃~60℃; humidity environment: 0~100%.

[0074] The present invention will be specifically described below through the following examples.

[0075] Example 1

[0076] The adhesive used in this embodiment is a 3D printing adhesive, TangoblackPlus.

[0077] This embodiment measures 180 joint samples at a time to complete the study of the effect of adhesive layer thickness and stress mode on adhesive performance. We set 12 groups of adhesive layer thicknesses in the range of 0.1mm to 1.6mm, and each group of thicknesses is divided into 15 tension-shear coupling stress modes with different proportions. Among them, we adjust the tension-shear coupling stress ratio of the adhesive layer by changing the angle of the joint θ0°~90°, such as Fig. 9 As shown, (a) is the distribution of 12 kinds of adhesive thicknesses, (b) is the arrangement diagram of different joint angles with a thickness of 0.4 mm at C in (a), (c) is a schematic diagram of lap shear test when θ=0°, (d) is a schematic diagram of pull-out test when θ=90°, (e) is a schematic diagram when θ=45°, and (f) is a schematic diagram of tensile shear stress decomposition. In the above figures, h is the adhesive thickness and F is the load.

[0078] The experimental results are as follows Fig.10 As shown, for the same adhesive, the bonding strength increases with the decrease of the bonding layer thickness, and the increase increases with the increase of the normal stress ratio.

[0079] It can be seen that the method of the present invention can test hundreds of test samples in a short period of time, and can test these samples simultaneously in one experiment, and can test the bonding performance under multiple force modes at the same time. Through automatic control and precise 3D printing technology, precise control of the bonding layer thickness, force mode and curing conditions is achieved, ensuring the consistency of sample preparation and high repeatability of experimental results. It integrates advanced image processing technology, can automatically collect data on the failure strength and failure mode of each sample, and perform rapid processing and analysis, which significantly improves the efficiency and accuracy of data acquisition.

[0080] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, they are also intended to be included.

Claims

1. A high-throughput test method for bonding strength, characterized in that: The following steps are involved: A test assembly (4) is prepared by using 3D printing technology, the test assembly (4) comprising two rectangular bars (1), a plurality of test specimens (2) being arranged in parallel between the two rectangular bars (1), each of the test specimens (2) comprising two test structures, each of the test structures comprising a first substrate (3-1), a second substrate (3-2) and a force measurement module (3-3), the force measurement module (3-3) being fixedly connected between the first substrate (3-1) and the second substrate (3-2), the first substrate (3-1) having an adhesive surface, the two adhesive surfaces being connected by an adhesive (3-4) to form a joint; The test component (4) is placed in a test environment, and a force is applied to the rectangular bar (1) so that the force measurement module (3-3) is stretched to generate strain until the joint fails in bonding; during the test, a video recording module is used to record the changes of the test component (4) throughout the test, and an image at the beginning of the test and an image at the time of bonding failure are obtained; An image processing module is used to process the image at the beginning of the test and the image at the time of adhesive failure, respectively, to obtain the length of each force measurement module (3-3) at the beginning of the test and at the time of adhesive failure, and to calculate the strain of the force measurement module (3-3) when the joint reaches the maximum load; The strain is substituted into the force-displacement curve of the force measurement module (3-3) to obtain the maximum load applied to the joint, and then the bonding strength of the joint is obtained.

2. The high-throughput bonding strength testing method according to claim 1, characterized in that: The adhesive (3-4) is a material for 3D printing or a material not for 3D printing; When the adhesive (3-4) is a material for 3D printing, the test component (4) is prepared as a whole by one 3D printing; When the adhesive (3-4) is a material not used for 3D printing, a first assembly (4-1) and a second assembly (4-2) are prepared respectively by using 3D printing technology, wherein the first assembly (4-1) and the second assembly (4-2) respectively include one rectangular strip (1) and a plurality of test structures; in the first assembly (4-1), the first substrate (3-1) of each test structure has a first bonding surface (A); in the second assembly (4-2), the first substrate (3-1) of each test structure has a second bonding surface (B); the first assembly (4-1) and the second assembly (4-2) are assembled through an assembly plate, and the first bonding surface (A) and the second bonding surface (B) are connected by using an adhesive (3-4) to form a joint.

3. The high-throughput bonding strength testing method according to claim 2, characterized in that: The assembly plate comprises a bottom plate (5), a surface of the bottom plate (5) having a plurality of first positioning strips (5-1) arranged in parallel along a length direction, and a space between two adjacent first positioning strips (5-1) is used to limit a test structure in the first assembly (4-1); The surface of the bottom plate (5) is also provided with a plurality of second positioning strips (5-2) arranged in parallel along the length direction, the second positioning strips (5-2) correspond to the first positioning strips (5-1) one by one, and the space between two adjacent second positioning strips (5-2) is used to limit a test structure in the second assembly (4-2); A plurality of positioning protrusions (5-3) arranged along the length direction of the bottom plate (5) are also arranged between the first positioning strip (5-1) and the second positioning strip (5-2); the plurality of positioning protrusions (5-3) are arranged close to one side of the first positioning strip (5-1); and the space between two adjacent positioning protrusions (5-3) is used to limit a first bonding surface (A); a limiting strip (5-6) is also arranged between the first positioning strip (5-1) and the second positioning strip (5-2); the limiting strip (5-6) is arranged close to one side of the second positioning strip (5-2) and is used to adjust the bonding thickness between the second bonding surface (B) and the first bonding surface (A); The two ends of the bottom plate (5) are respectively provided with first limiting grooves (5-4) on one side of the first positioning strip (5-1), and the two first limiting grooves (5-4) are used to limit the rectangular strip (1) in the first assembly (4-1); the two ends of the bottom plate (5) are respectively provided with second limiting grooves (5-5) on one side of the second positioning strip (5-2), and the two second limiting grooves (5-5) are used to limit the rectangular strip (1) in the second assembly (4-2).

4. The high-throughput bonding strength testing method according to claim 3, characterized in that: The assembling method of the first assembly (4-1) and the second assembly (4-2) comprises the following steps: After the first bonding surface (A) is dipped in the adhesive (3-4), the test structures in the first assembly (4-1) are respectively placed between the first positioning strips (5-1); when the rectangular strip (1) in the first assembly (4-1) is limited by the two first limiting grooves (5-4), the first bonding surface (A) is placed between adjacent positioning protrusions (5-3); After the second bonding surface (B) is dipped in the adhesive (3-4), the test structures in the second assembly (4-2) are respectively placed between the second positioning strips (5-2). When the rectangular strip (1) in the second assembly (4-2) is limited by the two second limiting grooves (5-5), the bottom surface of the second bonding surface (B) is placed on the limiting strip (5-6) and contacts the first bonding surface (A) for bonding.

5. The high-throughput bonding strength testing method according to claim 1, characterized in that: The test background is black, the first substrate (3-1) and the second substrate (3-2) are white, and the processing method of the image processing module comprises the following steps: The video obtained by the video recording module is captured frame by frame using the screenshot software, and each image is processed into a matrix using MATLAB. Each element in the matrix represents the grayscale of a pixel. Then the elements of the matrix are binarized: 255 represents a grayscale pixel close to white, and 0 represents a grayscale pixel close to black. Based on a white first substrate (3-1) and a white second substrate (3-2), all pixels with grayscale values ​​lower than 200 are set to 0; an image of the first substrate (3-1) is extracted to locate the left and right boundaries of each test sample (2); an image of the white second substrate (3-2) is extracted to locate the upper and lower boundaries of each test sample (2); By obtaining the left and right boundaries and the upper and lower boundaries of each test sample (2), the position information of each test sample (2) is determined, and the image of the test sample (2) is extracted according to the position information of each test sample (2) and placed in a matrix, the upper and lower boundaries of the force measurement module (3-3) in each test sample (2) are obtained, and the length of the force measurement module (3-3) in each test sample (2) is calculated.

6. The high-throughput bonding strength testing method according to claim 5, characterized in that: The method for locating the left and right boundaries of each test sample (2) is as follows: summing the grayscale image columns to obtain the total grayscale pixel value of each column; in two adjacent columns, from left to right, when the total grayscale pixel value changes from small to large, it is the left boundary of a sample (2); when the total grayscale pixel value changes from large to small, it is the right boundary of a sample (2).

7. The high-throughput bonding strength testing method according to claim 5, characterized in that: The method for obtaining the upper and lower boundaries of each test sample (2) is: summing the grayscale image row by row to obtain the total grayscale pixel value of each row. In two adjacent rows, from top to bottom, when the total grayscale pixel value changes from small to large, it is the upper boundary of a sample (2); when the total grayscale pixel value changes from large to small, it is the lower boundary of a sample (2).

8. The high-throughput bonding strength testing method according to claim 1, characterized in that: The first substrate (3-1) and the second substrate (3-2) are made of a rigid resin material by 3D printing, and the force measurement module (3-3) is made of a 3D-printed linear elastic material.

9. The high-throughput bonding strength testing method according to claim 1, characterized in that: The test method is used to optimize the preparation parameters of the adhesive, and the adhesives in the plurality of test samples (2) are prepared respectively with different parameters; or: The test method is used to explore the influence of adhesive thickness and different stress modes on adhesive failure strength and failure mode. At this time, a plurality of test specimens (2) are grouped so that the adhesives in each group have different thicknesses. The adhesives in the same group have the same thickness, but the joints have different bonding angles.

10. The high-throughput bonding strength testing method according to claim 1, characterized in that: During the test, the temperature of the test environment is controlled to be -20°C to 60°C; the humidity environment is controlled to be 0 to 100%.

Citation Information

Patent Citations

  • Method for measuring interface bonding strength of thermal barrier coating layer

    CN107345898A

  • Paper elasticity modulus testing method based on speckle printing

    CN107655756A

  • Analysis method for deformation and damage of bonding surface of concrete repairing material

    CN114739826A

  • Method for testing long-term creep property of adhesive by adopting tensile shear sample

    CN119000340A

  • Material testing machine

    JP2004257925A